PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA MELALUI PENDEKATAN CONTEXTUAL TEACHING AND LEARNING PADA MATERI BARISAN DAN DERET UNTUK SISWA SMA/MA KELAS XI - Wulan Dari; Nahor Murani Hutapea; Atma Murni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The background of this research is the restrict of mathematic learning device as supporting learning referring to 2013 Curriculum. This research aims to developed the lesson plan and students worksheet of mathematics which refers to of Contextual Teaching and Learning on the subject sequence and series for 11th grade students of Senior High School with valid and practical criteria. This study method used in 4D model by Thiagarajan, that consist of define, design, development, and disseminate, because of time and cost, the study was only to development step. The lesson plan and students worksheet of mathematics that had been developed than validated by three validatores and revised based on the input from validators. The valid students worksheet then tested in two stages, the small group trial (7 students of class XI IPA1 SMA Negeri 9 Pekanbaru) and large group trial (39 students of class XI IPA2 SMA Negeri 9 Pekanbaru). Based to the data analysis and discussion can be concluded that the lesson plan and students worksheet of mathematics which refers to application of Contextual Teaching and Learning on the subjects sequence and series are valid with and average value for the lesson plan is 3.61 and the average value for students worksheet is 3.54. The student worksheet has also reached the practical qualification in mean percentage of student responses 88,84% in large group trial with very practical. Based on the results of this research can be concluded that the product in the form of Lesson Plan and Student Worksheet mathematics which refers to Contextual Teaching and Learning on the subject Sequence and Series for 11th grade students of Senior High School is considered very valid and practical.Key Words: Validity and Practicality, Research and Development, Contextual Teaching and Learning, Sequence and Series